Autoeficacia emocional y bienestar en médicos de un hospital de alta complejidad en Lima, 2025 - Pereira-Alagón, Miguel (2025)
Objective. To determine the relationship between emotional self-efficacy and well-being in physicians at a high-complexity hospital in Lima, Peru. Methods. A quantitative, basic-type study with a non-experimental, correlational, and cross-sectional design. The population consisted of 100 physicians from a high-complexity hospital, with a census-based sample. Two separate instruments were used to measure each variable, both validated and reliable. Spearman’s rho and the p-value were used to test the hypotheses. Results. Emotional self-efficacy was most frequently rated at a moderate level (49.0%), and well-being was also most commonly reported at a moderate level (66.0%). A significant positive correlation was found between emotional self-efficacy and well-being (rho = 0.899; p-value = 0.000). Conclusions. There is a significant relationship between emotional self-efficacy and well-being in physicians at a high-complexity hospital, both overall and across each of their respective dimensions.